Health literacy and health outcomes in hypertension: An integrative review - Shaoying Du; Yi Zhou; Cong Fu; Yan Wang; Xiaojing Du; Ran Xie (Elsevier, 2018)
Objective: The aim of this study was to summarize the evidence of health literacy and health outcomes in hypertensive patients. Methods: Articles published in English were searched from six databases: MEDLINE, CINAHL, Embase, ERIC, psycINFO, and SCOPUS. The articles published up to September 2017 were included. Results: Nineteen publications were included in the review. There was quality and consistent evidence that hypertensive patients with lower literacy had poorer knowledge. There was inconsistent evidence to show the relationship between health literacy and clinical outcomes, of systolic and diastolic blood pressure, and blood pressure control; behavioral outcomes, of self-care, self-efficacy, adherence; patient-physician interactions outcomes, of patient-physician communication, patient trust, involvement in decision making and other outcomes. Conclusion: The person with low health literacy is likely to have poor knowledge of hypertension. However, there is insufficient evidence to suggest that health literacy is associated with outcomes of hypertension independently. Keywords: Health literacy, Hypertension, Outcomes, Integrative review